2015
DOI: 10.1038/srep16376
|View full text |Cite
|
Sign up to set email alerts
|

Association of specific frequency bands of functional MRI signal oscillations with motor symptoms and depression in Parkinson’s disease

Abstract: A novel empirical mode decomposition method was adopted to investigate the dissociative or interactive neural impact of depression and motor impairments in Parkinson’s disease (PD). Resting-state fMRI data of 59 PD subjects were first decomposed into characteristic frequency bands, and the main effects of motor severity and depression and their interaction on the energy of blood-oxygen-level-dependent signal oscillation in specific frequency bands were then evaluated. The results show that the severity of moto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Active forced expiration, which is the motoric component, induced significant neural responses in motor control areas in healthy controls, including the bilateral motor cortices, supplementary motor area, cerebellar, and striatum (Figure a); however, these areas showed less activation in HF subjects (Figure b,c), indicating less involvement in motor control. The disruption of the striatal‐cortical‐cerebellar circuit will result in ataxia, difficulties in smooth pursuit of action, and other movement disorders (Hu, Song, Li, et al, ; Song et al, ). HF patients show multiple motoric impairments, such as dysfunctions in complex planning, spatial attention, motor speed, grip strength, and gait (Davies, Greig, Jordan, Grieve, & Lipkin, ; Notarius et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Active forced expiration, which is the motoric component, induced significant neural responses in motor control areas in healthy controls, including the bilateral motor cortices, supplementary motor area, cerebellar, and striatum (Figure a); however, these areas showed less activation in HF subjects (Figure b,c), indicating less involvement in motor control. The disruption of the striatal‐cortical‐cerebellar circuit will result in ataxia, difficulties in smooth pursuit of action, and other movement disorders (Hu, Song, Li, et al, ; Song et al, ). HF patients show multiple motoric impairments, such as dysfunctions in complex planning, spatial attention, motor speed, grip strength, and gait (Davies, Greig, Jordan, Grieve, & Lipkin, ; Notarius et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Another common comorbid characteristic of HF is high incidence of depression or depressive symptoms (40–60%) (Jiang et al, ). Several brain regions, including the middle and posterior cingulate cortices, vMPFC, and parietal areas, are damaged in subjects with depression (Hu, Song, Li, et al, ; Song et al, ). Brain tissue changes in these sites would exert prominent emotional and behavioral effects on HF subjects as reported in the condition (Hou, Song, et al, ; Hou, Sui, Song, & Yuan, ; Hou, Wang, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Resting‐state functional MRI techniques have been widely applied in various clinical studies of psychiatric symptoms and other neurological issues (Hu, Song, Li, et al., ; Hu, Song, Yuan, et al., ; Song et al., ), and thus, may be useful in assessing network‐level changes in OSA subjects. Functional connectivity (FC), a measurement that quantifies statistical dependency between the functional time series of anatomically distinct brain sites, is a robust way to assess functional network integrity.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, many structural and functional neuroimaging studies have attempted to explore the possible mechanisms of depression in PD 8 9 10 11 12 13 14 15 16 . Structural neuroimaging studies showed that PD patients with depression displayed grey matter loss and white matter reduction in the prefrontal, temporal and some limbic regions 8 9 10 .…”
mentioning
confidence: 99%